Features of mental disorders in victims of violent action - Shum Сергій (Psychosomatic Medicine and General Practice, 2020)
Objective. Victims of violent crimes, regardless of the way the crime affects the victim - psychological, financial, physical, and spiritual - can have significant psychosomatic health problems for a long time. The dangers of violence, including torture and other ill-treatment, were highlighted in the Istanbul Protocol, which is an international guide to the effective investigation and documentation of torture and other cruel, inhuman, or degrading treatment or punishment. Methods and materials. A pilot study was conducted to verify the mental disorders of 22 victims of violent crimes according to forensic psychiatric examinations. Verification of mental disorders was carried out in accordance with the provisions of the Istanbul Protocol and the criteria of the International Classification of Diseases (ICD-10). Results. All subjects reported traumatic events that met the stress criterion (A) for PTSD. 63.6% of the victims were prisoners in the temporarily occupied territories of Donbas, where they were subjected to torture and other inhuman treatment; 18.1% were victims of police violence; 18.1% were victims of sexual violence. According to the PTSD criteria, 100% of the subjects showed manifestations of the intrusion cluster, 54.5% - manifestations of the numbing cluster, and 31.8% - manifestations of the hyperexcitation cluster. 31.8% of victims were diagnosed with PTSD. More than 1/3 of the subjects showed signs of depression, but only 9.1% met the criteria for moderate depressive disorder. Anxiety was a pervasive symptom present at the same time as other disorders in 95.5% of cases. Symptoms of somatization (15 people; 68.1%) were mainly chronic pain of various localizations. Alcohol consumption at the level of domestic drunkenness was 40.9%, occasional cannabis use - 27.2%. Mental disorders due to violence can remain at the level of fragmentary or subclinical manifestations of mental disorders, not reaching the nosological level and reduce over time, as well as be the initial or residual phase of a certain mental disorder. Conclusions. Early diagnosis of mental disorders in victims of violent crimes will allow the timely application of medical and psychosocial measures, which will accelerate the rehabilitation of victims and reduce mental illness